Magnetic moment distribution of magnetic cataclysmic variables - Wu, Kinwah; Wickramasinghe, Dayal T. (Monthly notices of the Royal Astronomical Society, 1991)
We have presented a simulation study or the relative numbers or the AM Herculis binaries and the intermediate polars as a function of the orbital period using random variables subject to suitable constraints to describe the various parameters. We show that the observations can be matched by a single distribution in the magnetic moment μ that is, Gaussian in logarithm space with $\langle \text {log}(μ/10^{33}\enspace \text{G cm}^{3})\rangle = 0.7 ± 0.3$. For such an ensemble the intermediate polars are distributed in the $\text{log}(P_\text{orb})-\text{log}(P_\text{s})$ diagram about the critical disc line but with a larger scatter than observed.